2008
DOI: 10.19030/tlc.v5i3.1300
|View full text |Cite
|
Sign up to set email alerts
|

On-Campus Versus Off-Campus: A Comparative Analysis Of MBA Learning Outcomes For A Classroom-Based Program

Abstract: Both direct and indirect measures of learning outcomes provide data that can be used to improve learning. The research reports a study of an indirect measure of learning outcomes in an MBA program. The measure was a Post-Then format using a five point Likert scale. Thirteen courses were analyzed generating 107,440 responses over a 5-year period. Two research questions were addressed: Are MBA students learning as demonstrated by an improvement in learning outcomes? and, Is there a difference in learning outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Barnes et al (2004) identified differences in the learning styles of the students and that students had preferences in certain course delivery methods over others. In another research paper Barnes et al (2008) also found that there may be differences in learning outcomes for certain courses when courses are offered at different locations. Tomlinson (1996) emphasizes the need for instructors to be aware of and adapt to student learning styles.…”
Section: Introductionmentioning
confidence: 96%
“…Barnes et al (2004) identified differences in the learning styles of the students and that students had preferences in certain course delivery methods over others. In another research paper Barnes et al (2008) also found that there may be differences in learning outcomes for certain courses when courses are offered at different locations. Tomlinson (1996) emphasizes the need for instructors to be aware of and adapt to student learning styles.…”
Section: Introductionmentioning
confidence: 96%